Characterization of Glyceridic and Unsaponifiable Compounds of Sacha Inchi (Plukenetia huayllabambana L.) Oils - Chasquibol Silva, Nancy Ascención (2014)
This work deals with the characterization of the main glyceridic and unsaponifiable components of oils obtained from Sacha inchi (Plukenetia huayllabambana L.) seed ecotypes collected during two harvests in the Department of Amazonas in Peru. The seed-oil yield was 30.3–41.2%; standing out are the high percentages of the ¿3- and ¿6-fatty acids series whose ranges lie within those of the present Regulation for Sacha inchi oils. Triacylglycerols with even equivalent carbon number (ECN; 36–42) were the main components. Minor glyceridic polar compounds such as oxidized triglycerides, diglycerides, monoglycerides, and free fatty acids were determined by high-performance size exclusion chromatography. The low campesterol/stigmasterol ratio (1:6), unusual in the majority of vegetable oils, stands out. Regarding aliphatic hydrocarbons, these oils showed a particular profile for the saturated series of odd and even carbon atom numbers. According to our results Sacha inchi P. huayllabambana oils can be offered as a good alternative to P. volubilis, the species mainly commercialized for this vegetable oil.